PERKEMBANGAN TAMAN KANAK-KANAK DI KOTA YOGYAKARTA 1930-1960 - , LUTHFIA FARHANI F ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research discusses about kindergarten education in Yogyakarta during the period of 1930s until 1960s. This research is based on an understanding of the small number of studies which asses the phenomenon of children's education in the colonial era in Indonesia. Whereas it will be better to present an optimally Indonesiasentris historiography by writing a review on kindergarten education which is necesarry to be presented to provide an understanding on the role of education toward the changes happening in society in the history generally. The development of kindergarten education in Yogyakarta during the colonial era before 1930s